Assistance of inertial microfluidics in membrane-based microfiltration - Zhang, Boran (2023)
Backwashing has been widely used in microfiltration to clear sludge cake formed on membrane surface. However, it was found to perform much below expectation if only few pores were clogged. For these conditions, other assistant methods preventing the clogging are needed. In this study, we propose a hydraulic assistance of secondary microfluidic vortex on concentrating extremely low dilution sample (0.1 CFU/mL). The secondary vortex can help to trap microparticles suspended, and also help to flush the settled ones. The optimal geometry of spiral channel was identified and validated in experiment. The results were remarkably improved, where a stable recovery rate around 95 % was obtained with a high concentration ratio of 100 (from 0.1 CFU/mL to 10 CFU/mL) within 1 h. To the state of art, there has been no application of inertial microfluidic techniques utilized on membrane-based microfiltration. For cellular microparticles, they may perform differently on in-pore deformation due to their viscoelastic physical characteristics. The applications on different bio-targets will be investigated separately in the further studies. The proposed method is promising in application of water quality assessment after chlorination in water treatment.